Ketidakamanan pekerjaan dan kinerja tugas: Peran burnout sebagai mediator - Alice Salendu; Muhamad Fachri Maldini (University of Muhammadiyah Malang, 2021)
An increasingly dynamic and uncertain job demands provided new challenges for employees in task performance, had an impact on job insecurity, and triggered burnout for employees. This study investigated the predictor role of job insecurity on task performance through the mediation role of burnout. The researcher conducted correlational research with a non-experimental research design. Data were collected from 106 respondents who were private employees with a minimum of one year of work experience. The sampling technique used was convenience sampling. This study was conducted by using the Job Insecurity Scale, Task Performance Scale, and Maslach Burnout Inventory - General Scale which was adapted in Indonesia language. The data were processed using multiple regression analysis with mediating variables. The result of this research showed that job insecurity had a negative relationship with task performance (b = −0.35, t = −2.78; p = 0.00). In addition, it was also found that burnout partially mediated the relationship between job insecurity and task performance (β = -0.20, SE =0.07; 99% CI [-0.41,-0.05]). There was evidence that job insecurity had a negative relationship with task performance and burnout had a mediating effect on the relationship between job insecurity and task performance.